Circulating androgen receptor combined with 18F-fluorocholine PET/CT metabolic activity and outcome to androgen receptor signalling-directed therapies in castration-resistant prostate cancer. Issue 1 (December 2017) - Conteduca, V.; Scarpi, E.; Caroli, P.; Salvi, S.; Lolli, C.; Burgio, S.; Menna, C.; Schepisi, G.; Testoni, S.; Gurioli, G.; Paganelli, G.; Casadio, V.; et al.
Abstract The association between choline uptake and androgen receptor (AR ) expression is suggested by the upregulation of choline kinase-alpha in prostate cancer. Recently, detection ofAR aberration in cell-free DNA as well as early 18F-fluorocholine positron emission tomography/computed tomography (FCH-PET/CT) were associated with outcome in metastatic castration-resistant prostate cancer (mCRPC) patients treated with abiraterone and enzalutamide. We aimed to make a direct comparison between circulatingAR copy number (CN) and choline uptake at FCH-PET/CT. We analysed 80 mCRPC patients progressing after docetaxel treated with abiraterone (n = 47) or enzalutamide (n = 33). We analysedAR CN from plasma samples using digital PCR and Taqman CN assays and total lesion activity (TLA) and metabolic tumor volume (MTV) on FCH-PET/CT at baseline. A meaningful correlation was showed amongAR gain and TLA/MTV compared toAR non-gained cases (P = 0.001 and P = 0.004, respectively), independently from type of treatment. Multivariate analysis revealed thatAR CN and only TLA were associated with both shorter PFS (P < 0.0009 and P = 0.026, respectively) and OS (P < 0.031 and P = 0.039, respectively). AR gain appeared significantly correlated with choline uptake represented mainly by TLA. Further prospective studies are warranted to better address this pathway of AR-signalling and to identify multiplex biomarker strategies including plasmaAR and FCH-PET/CT in mCRPC patients.